Neuropeptide Y (NPY) potentiates phenylephrine-induced mitogen-activated protein kinase activation in primary cardiomyocytes via NPY Y5 receptors - Pellieux, Corinne (The National Academy of Sciences, 2000)
Neuropeptide Y (NPY) has been shown to participate in the cardiovascular response mediated by the sympathetic system. In this report, we investigate the growth factor properties of NPY on cardiac myocytes. Mitogen-activated protein kinases (MAPK) are key signaling molecules in the transduction of trophic signals. Therefore, the role of NPY in inducing MAPK activation was studied in mouse neonatal cardiomyocytes. Exposure of neonatal cardiomyocytes to either NPY, phenylephrine, or angiotensin II induces a rapid phosphorylation of the extracellular responsive kinase, the c-jun N-terminal kinase, and the p38 kinase as well as an activation of protein kinase C (PKC). Moreover, NPY potentiates phenylephrine-induced MAPK and PKC stimulation. In contrast, NPY has no synergistic effect on angiotensin II-stimulated MAPK phosphorylation or PKC activity. NPY effects are pertussis toxin-sensitive and calcium-independent and are mediated by NPY Y5 receptors. Taken together, these results suggest that NPY, via G(i) protein-coupled NPY Y5 receptors, could participate in the development of cardiac hypertrophy during chronic sympathetic stimulation by potentiating α-adrenergic signals.